Posttraumatic Stress Disorder in Children and Adolescents and Evaluation in Forensic Medicine - Karakaya, Işık; Çolak, Başar (The Bulletin of Legal Medicine, 2007)
Posttraumatic stress disorder (PTSD) is one of the common disorders after the destructive traumatic experiences. PTSD associated traumas mostly have forensic properties and are handled by forensic medicine and psychiatry together. It is known that children and adolescents present different clinical conditions than adults and might not be accurately diagnosed because the symptoms are subliminal. In this paper, we tried to emphasize the clinical properties of PTSD, the evaluation and the importance of PTSD for forensic medicine. Key words: Child, adolescent, PTSD, forensic evaluation.